2009
DOI: 10.1111/j.1468-1331.2009.02534.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ginsenoside‐Rd for acute ischaemic stroke: a randomized, double‐blind, placebo‐controlled, phase II multicenter trial

Abstract: Ginsenoside-Rd may be of some benefit in acute ischaemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 29 publications
0
50
0
Order By: Relevance
“…Our previous in vitro and in vivo studies have demonstrated that GSRd has neuroprotective effects on injured neurons (Ye et al 2008;Liu et al 2009;Ye et al 2009;Ye et al 2011a;Ye et al 2011b). In the present study, we showed that GSRd attenuated glutamate-and NMDA-induced excitotoxic injury of cultured rat hippocampal neurons by inhibiting Ca 2?…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our previous in vitro and in vivo studies have demonstrated that GSRd has neuroprotective effects on injured neurons (Ye et al 2008;Liu et al 2009;Ye et al 2009;Ye et al 2011a;Ye et al 2011b). In the present study, we showed that GSRd attenuated glutamate-and NMDA-induced excitotoxic injury of cultured rat hippocampal neurons by inhibiting Ca 2?…”
Section: Discussionmentioning
confidence: 96%
“…In our randomized, double-blind, placebo-controlled, phase II multicenter trial, we found that GSRd shows efficacy and safety for the treatment of acute ischemic stroke (Liu et al 2009). Moreover, we found that GSRd can attenuate the cytotoxicity of PC12 cells induced by hydrogen peroxide, protect against the injury of cultured hippocampal neurons induced by oxygen-glucose deprivation (Ye et al 2008;Ye et al 2009), and attenuate apoptosis and inflammation after transient focal ischemia (Ye et al 2011a;Ye et al 2011b).…”
Section: Introductionmentioning
confidence: 96%
“…Various research studies as well as clinical trials have been conducted to examine the effect of various antiinflammatory treatments after ischemic stroke (Table 2). While two of these studies report better outcomes with their antiinflammatory treatment, 91,92 the remaining studies report worse outcomes, 93,94 no difference between treatment and placebo, [95][96][97][98] or were simply safety studies [99][100][101] with all of them failing to make it beyond clinical phase trials. Importantly, some of these studies were underpowered to detect a meaningful clinical effect.…”
Section: Antiinflammatory Treatment Strategiesmentioning
confidence: 99%
“…Currently Rd is being developed to treat patients with acute ischemic stroke. Several studies have been reported demonstrating the pharmacokinetics [35], safety [36], and preliminary efficacy [37] of Rd in human subjects. More recently, a phase III multicenter clinical trial of Rd showed a benefit in terms of the prespecified primary endpoint, the distribution of disability as measured by the modified Rankin score at 90 days after stroke onset.…”
Section: Discussionmentioning
confidence: 99%